Comparison of Lasix and Methyldopa in Controlling Hypertension in preeclampsia patients: A Double-Blind Randomized Clinical Trial - Siamansoori, Setareh; Afshari, Elahe; Palizdar, Maryam; Hosseini, Mohammad Ali (Archives of Men's Health, 2020)
Introduction: Preeclampsia is a specific gestational syndrome that reduces organ perfusion due to vascular spasm and endothelial activation. Despite the use of magnesium sulfate, the patient's blood pressure sometimes remains uncontrolled, and therefore, it is necessary to use other medications, especially diuretics and Methyldopa. Hence, the aim of this study was to compare Lasix and Methyldopa in controlling postpartum hypertension in preeclampsia patients after magnesium sulfate treatment. Material and Methods: This double-blind randomized clinical trial was carried out on 100 women with preeclampsia referred to Akbar Abadi Hospital-Iran. In the first 24 hours after the termination of pregnancy, the participants’ blood pressure was measured and those with a blood pressure of 140/90 to 160/100 were divided into two groups. In the first and second 24 hours, and then one week after the intervention, systolic and diastolic blood pressure as well as diuresis and drug complications in the two groups were assessed and compared. The present study was registered in the Iranian Registry of Clinical Trials (IRCT) under the ID of IRCT20180114038349N1. Results: The mean age of individuals was 29.93 ± 6.65 in the Methyldopa group, and 32.35 ± 4.85 in the Lasix group (P = 0.479). Systolic and diastolic blood pressure had a substantial reduction in both groups, but there was no significant difference between the two groups (P> 0.05). Systolic blood pressure was reduced by 31 mmHg (reduction from 146 to 115) in the methyldopa group and 30 mmHg (reduction from 145 to 114) in the Lasix group. Furthermore, the reduction in diastolic blood pressure was 25 mmHg (from 95 to 70) in the methyldopa group, and 21 mmHg in the Lasix one (from 91 to 70). Conclusion: The present study showed that using Lasix and methyldopa was effective enough in changing blood pressure in patients with preeclampsia, and the effects observed in the two groups were the same. Therefore, it could have a great impact on the wellbeing of couples.